Evaluating Fieldwork and a Targeted Curriculum on Urban Counselor Trainees' Self-Efficacy. (June 2015) - Hayden, Laura; Cook, Amy; Gracia, Robert; Silva, Meghan Ray; Cadet, Melanie
This study explored counseling trainees' development of self-efficacy within an urban high school practicum experience. The following two research questions were addressed: (a) Did a field placement experience in an urban school increase counseling trainees' self-efficacy? and (b) What fieldwork factors affected counseling trainees' development of self-efficacy as urban counselors? Quantitative analysis indicated that participants self-reported overall improvement in counseling skills and greater confidence in executing school counseling activities in an urban environment, while qualitative analysis suggested the positive impact of using a targeted supervisory curriculum to develop counseling students' self-efficacy in working with urban youth. Implications for counselor educators are provided.